Meeting points between Paulo Freire pedagogical focus and Human Rights Education (Revista Posgrado y Sociedad, 2020)
Paulo Freire's pedagogical approach generates the elements both for an education for the social change and towards the approach of Human Rights Education. This essay proposes as objectives, first, to delve into the elements included in the Human Rights Education approach; second, to expose the main concepts of Paulo Freire's pedagogy and, third, to demonstrate that the approach to Human Rights Education is one of the most concrete ways of linking between trends in education and Paulo Freire's pedagogy. Human Rights Education is aimed at making the person a subject of law, with a great capacity for critical questioning society, which manages to become an agent of social change, committed to the fulfillment of human rights. To achieve this path, you need a teacher who educates for criticism and for change, through dialogue. The methodology used for the preparation of this document consisted of a review and in-depth analysis of the texts on the subject. It was concluded that both educational approaches have fundamental coincidences on the essence of education and the educational fact.
Keywords: Paulo Freire; pedagogy of hope; Education in Human Rights; subject of law; educational dialogue